2016
DOI: 10.1002/ijc.30528
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic circulating concentrations of plasma insulin‐like growth factor‐I and risk of lymphoma in the European Prospective Investigation into Cancer and Nutrition

Abstract: Insulin‐like growth factor (IGF)‐I has cancer promoting activities. However, the hypothesis that circulating IGF‐I concentration is related to risk of lymphoma overall or its subtypes has not been examined prospectively. IGF‐I concentration was measured in pre‐diagnostic plasma samples from a nested case–control study of 1,072 cases of lymphoid malignancies and 1,072 individually matched controls from the European Prospective Investigation into Cancer and Nutrition. Odds ratios (ORs) and confidence intervals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Moreover, a moderately large sample size allowed us to make reasonably precise estimates of the relationship between circulating IGF‐I concentrations and bladder cancer, while information on tumour subtypes enabled us to explore possible heterogeneity in bladder cancer risk by tumour aggressiveness. Finally, the distribution of circulating IGF‐I concentrations among controls in this study was similar to that observed in previous prospective studies …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, a moderately large sample size allowed us to make reasonably precise estimates of the relationship between circulating IGF‐I concentrations and bladder cancer, while information on tumour subtypes enabled us to explore possible heterogeneity in bladder cancer risk by tumour aggressiveness. Finally, the distribution of circulating IGF‐I concentrations among controls in this study was similar to that observed in previous prospective studies …”
Section: Discussionsupporting
confidence: 89%
“…Finally, the distribution of circulating IGF-I concentrations among controls in this study was similar to that observed in previous prospective studies. 20,21 This study has some limitations. First, the analysis relied on a single measurement of circulating IGF-I in each participant.…”
Section: Discussionmentioning
confidence: 95%
“…In particular, IGFs are powerful hormones that have been associated with growth, survival, apoptosis and migration of multiple myeloma cells (Vishwamitra et al , ) but data on CLL are both sparse and conflicting. To date, only one prospective study from the European Prospective Investigation into Cancer and Nutrition (EPIC) of 184 CLL cases and three very small case‐control studies (27, 77 and 43 CLL cases with 17, 27 and 21 controls, respectively) have been published on this topic (Schillaci et al , ; Molica et al , ; Ayer et al , ; Perez‐Cornago et al , ). No association between CLL and IGF‐I levels was observed in the EPIC study (Perez‐Cornago et al , ) and only one unpowered study (N = 47) has examined IGFBP‐3 in relation to CLL (Ayer et al , ) (summary in Table SI).…”
Section: Odds Ratios For Chronic Lymphocytic Leukaemia (Cll) In Relatmentioning
confidence: 99%
“…The stronger scientific evidence to date has been provided by the EPIC study, reporting no association between CLL and IGF‐I levels in samples taken up to 13 years before diagnosis (Perez‐Cornago et al , ). Hence, our findings might be due to reserve causality and IGF‐I levels might be a marker of disease progression (Molica et al , ).…”
Section: Odds Ratios For Chronic Lymphocytic Leukaemia (Cll) In Relatmentioning
confidence: 99%
“…Primary thyroid lymphoma (PTL) is a rare thyroid tumour, representing approximately 5% of all thyroid malignancies and accounting for less than 2% of extranodal malignant lymphomas [1][2][3]. Despite the rarity of PTL, it is important to recognise PTL promptly because of different management of all the other thyroid neoplasms [4].…”
Section: Introductionmentioning
confidence: 99%